Pengembangan Media Pembelajaran Berbasis Google Workspace Dengan Optimalisasi Akun Belajar.id - Silvi Rahmawati; Muhammad Ridwan Effendi; Dyah Wulandari (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2022)
Education is one aspect that is used as a forum to shape the morals and behavior of the nation's children. Therefore, today's education requires each of its components to carry out their duties and roles well. Likewise with educators who must always develop learning both from the strategy or the media used. The objectives of this study include: (1) How to develop online learning media, (2) What are the advantages of developing online learning media, (3) What are the obstacles and solutions in developing online learning media at SMKN 2 Purwakarta. This study uses a qualitative approach with a descriptive method. The type of data used is primary and secondary data with data collection techniques using observation, interviews, and documentation. Testing the validity of the data with extended observations, triangulation, and discussions with colleagues. The theory used according to Sadirman about the teacher's role as a mediator, as well as the theory of learning media development using the ADDIE model. Based on the research results, first, the development of online learning media at SMKN 2 Purwakarta is in accordance with the ADDIE development model by optimizing the use of google workspace media with the learning.id account facility provided by the Ministry of Education and Culture. Second, the advantages of development include: Increasing effectiveness and efficiency in learning, Students are able to create something new, Encouraging students to express ideas, Encouraging teachers to be more creative, Expanding learning opportunities, Improving the quality of teaching and learning, Facilitating the formation of skills, Encouraging learning lifelong sustainability, Improving policy planning and management, Reducing the digital divide. Third, the obstacle to developing online learning media is the lack of knowledge about online learning media, while the solution is in several ways, including: Establishing the right strategy, providing training and always sharing with other school teacher friends through social media.